2014
DOI: 10.3390/ijerph110201626
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Choice to Drink Bottled Water and Tap Water in Rural Saskatchewan

Abstract: A cross-sectional study investigated risk factors associated with choices to drink bottled water and tap water in rural Saskatchewan. Of 7,500 anonymous postal questionnaires mailed out, 2,065 responses were analyzed using generalized linear mixed models. Those who reported a water advisory (p < 0.001) or living in the area for ≤10 years (p = 0.01) were more likely to choose bottled water. Those who reported tap water was not safe to drink were more likely to choose bottled water, an effect greater for those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
5
28
1
1
Order By: Relevance
“…However, less than one-quarter of participants drank water straight from the tap at home and were satisfied with the quality of tap water they did drink. Despite the lower reported prevalence of tap water consumption in our study compared with previous Canadian reports from Indigenous and other rural communities [16,17], the satisfaction with tap water in our sample was similar to that in a study among Indigenous communities in Canada [16]. Improvements in on-reserve water quality and access to more information about water testing have led to increasing levels of trust in water quality among Indigenous residents who drink tap water [16].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, less than one-quarter of participants drank water straight from the tap at home and were satisfied with the quality of tap water they did drink. Despite the lower reported prevalence of tap water consumption in our study compared with previous Canadian reports from Indigenous and other rural communities [16,17], the satisfaction with tap water in our sample was similar to that in a study among Indigenous communities in Canada [16]. Improvements in on-reserve water quality and access to more information about water testing have led to increasing levels of trust in water quality among Indigenous residents who drink tap water [16].…”
Section: Discussionsupporting
confidence: 60%
“…Improvements in on-reserve water quality and access to more information about water testing have led to increasing levels of trust in water quality among Indigenous residents who drink tap water [16]. A study in rural Saskatchewan found that living in the same area for more than 10 years and not experiencing water advisories were factors associated with daily tap water consumption [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Choices about drinking water consumption are governed by a complex set of factors related to sensory perception; risk perception; and economic, psychological and social issues, including media reports and marketing messages. 13 Walters and colleagues recommended exploring social or other underlying determinants of risk, such as community perceptions of the problem, to allow better mitigation of the risk. 12 …”
Section: Nsw Government Initiativesmentioning
confidence: 99%
“…The systems are open and vulnerable to environmental conditions and surrounding land use activities, making the water quality variable and sometimes unpredictable (Cessna et al 2015;Delpla et al 2015;Gough et al 2016;McLeod et al 2014). One concern is the threat posed by waterborne pathogens, such as Campylobacter, Legionella and various enteropathogenic coliforms, such as E. coli and Shigella, which can be introduced into watersheds by runoff from agricultural lands contaminated with animal wastes (Ferguson et al 2003;Leclerc et al 2002;World Health Organization 2011).…”
mentioning
confidence: 99%